Stress behaviour and physiology of developing Arctic barnacle goslings (Branta leucopsis) is affected by legacy trace contaminants. Issue 1893 (12th December 2018) - Scheiber, Isabella B. R.; Weiß, Brigitte M.; de Jong, Margje E.; Braun, Anna; van den Brink, Nico W.; Loonen, Maarten J. J. E.; Millesi, Eva; Komdeur, Jan
Abstract : Natural populations are persistently exposed to environmental pollution, which may adversely impact animal physiology and behaviour and even compromise survival. Responding appropriately to any stressor ultimately might tip the scales for survival, as mistimed behaviour and inadequate physiological responses may be detrimental. Yet effects of legacy contamination on immediate physiological and behavioural stress coping abilities during acute stress are virtually unknown. Here, we assessed these effects in barnacle goslings ( Branta leucopsis ) at a historical coal mine site in the Arctic. For three weeks we led human-imprinted goslings, collected from nests in unpolluted areas, to feed in an abandoned coal mining area, where they were exposed to trace metals. As control we led their siblings to feed on clean grounds. After submitting both groups to three well-established stress tests (group isolation, individual isolation, on-back restraint), control goslings behaved calmer and excreted lower levels of corticosterone metabolites. Thus, legacy contamination may decisively change stress physiology and behaviour in long-lived vertebrates exposed at a young age.